Global trade in final goods and intermediate inputs: Impact of FTAs and reduced "border effects" - Sebastian Franco-Bedoya; Erik Frohm (European Central Bank (ECB), 2020)
International trade in manufacturing goods has risen strongly over the past decades, contributing to the expansion of global value chains (GVCs). This paper studies how two factors contributed to this rise since 1970: (i) declining "border effects" that are arguably related to the ICT revolution that started around 1985, and (ii) the implementation of Free Trade Agreements that have gotten deeper over time. We take advantage of the identification of the time dimension in a panel setting to capture the emergence of GVCs by disentangling domestic and international trade in final goods and intermediate inputs. According to our results, diminished border effects account for the bulk of the increase in international trade in manufactured goods. The cost of a national border is estimated to have fallen by around 10% per year for total manufacturing trade since the 1970s. The decline has been 13% per year for exports of final goods and 8% for intermediate inputs, highlighting the importance of reduced border effects for enabling international trade in the age of GVCs. Moreover, we show that it is important to control for different border effects for final goods and intermediate inputs when estimating the trade impact of FTAs in gravity equations. With this enhancement, our results suggest that FTAs increase trade by 54% after ten years. We also find evidence that FTAs that are more recent have a greater trade effect than those signed in earlier periods.
Keywords: F13; F14; F15; F23; 330; Border effect; Free trade agreements; international trade; global valuechains